Balancing the roles of Employee Aad Primary Child Caregiver: Experiences of Single Mothers formally Employed in Otjiwarongo, Namibia - Markus, Julia Ndeyapewa (University of the Witwatersrand, Johannesburg, 2020)
The number of single mothers entering the workforce is an ever-increasing trend throughout the world, including countries in sub-Saharan Africa, such as Namibia. Usually, single mothers face many challenges fulfilling the roles of employee and primary caregiver simultaneously. Although the challenges experienced by employed, single mothers have been well researched in developed Western and European countries, there is a gap of knowledge regarding how formally employed, single mothers in sub-Saharan Africa, including Namibia, experience trying to balance the responsibilities of employee and primary caregiver of their children. Occupational social workers can play a meaningful role in supporting employees in the workplace, including employed, single mothers who are facing caregiving challenges that are negatively impacting on their work responsibilities. The main aim of this research was thus to explore how employed single mothers in Namibia experience trying to balance the roles of primary caregiver and employee, so that key role players within the workplace, especially occupational social workers, can gain more insight into how these challenges can best be addressed. To realise this aim, a qualitative research approach was adopted using the phenomenological research design. Fifteen employed mothers in Otjiwarongo, a small town of about 28 000 inhabitants in the Otjozondjupa region, were purposively selected as the research sample. Data were gathered by conducting individual interviews with the participants. The research tool was pre-tested with an employed single mother who met the sample selection criteria. Thematic analysis was employed to analyse data. The main findings based on data analysis were that fulfilling the role of mother is difficult when facing work pressure and working long hours. Stress experienced in the work environment is often carried over to the home environment, and vice versa. Focus on work activities can also be undermined when experiencing concerns about the well-being of their children, especially if they are young. Women try to balance their simultaneous roles by employing reliable caregivers to take on the responsibility of caregiving when they are at work. Based on research findings, it is recommended that occupational social workers work towards implementing policy and practice within the work environment that facilitates personal contact between mother and child.
Keywords: Occupational social worker; Work-life balance; Work-life conflict; Parenting stress; Boundary/border theory; Primary caregiver; SDG-3: Good health and well-being